Dickens's London : perception, subjectivity and phenomenal urban multiplicity - Wolfreys, Julian, 1958- (Edinburgh critical studies in Victorian culture., 2012)
Taking Walter Benjamin's Arcades Project as its model, Dickens's City offers an exciting and original project that opens a dialogue between phenomenology, philosophy and the Dickensian representation of the city in all its forms. Julian Wolfreys suggests that in their representations of London - its streets, buildings, public institutions, domestic residences, rooms and phenomena that constitute such space - Dickens's novels and journalism can be seen as forerunners of urban and material phenomenology. While also addressing those aspects of the urban that are developed from Dickens's interpretations of other literary forms, styles and genres, Dickens's City presents in twenty-six episodes (from Bells, Bridges and Butlers via Inns and Interiors and Public Houses, the Police and the Post to Todgers and the Thames) a radical reorientation to London in the nineteenth century, the development of Dickens as a writer, and the ways in which readers today receive and perceive both. Key Features Major reassessment of Dickens's writing on the city Dual focus on methodology and the historicity of Dickensian urban consciousness Philosophical reflections on urban tropologies through key passages from Dickens's texts recreate the experience of Victorian London Inventive structure offers the reader an experience of the disordered multiplicity of London Illustrated with 19 maps and photographs